Forkhead Box O1 Promotes Osteogenic Differentiation of Periodontal Ligament Stem Cells in Hypoxia/Reoxygenation Environments by Regulating Heme Oxygenase-1 Scavenging of Reactive Oxygen Species - Yujia Ye; Jinqiao Tang; Jiahui Ye; Bin Zhao; Yanning Ma (International Dental Journal, 2025)
Introduction and aims: Oral health is closely linked to systemic health, and patients with obstructive sleep apnea suffer from an increased risk of periodontitis due to repeated cycles of hypoxia/reoxygenation (H/R). This study aimed to assess the role of forkhead box O1 (FoxO1) in alveolar bone remodelling and explore how it affects H/R in vitro. Methods: The AnaeroPack system was employed to establish an H/R model based on periodontal ligament stem cells (PDLSCs). Using alkaline phosphatase (ALP) staining, ALP activity test, alizarin red staining, and RT-qPCR, the osteogenic differentiation capacity of PDLSCs was detected under the H/R environment. The expression of FoxO1 was specifically knocked down and overexpressed using small interfering RNA and lentiviral transfection to investigate the role of FoxO1 in the osteogenic differentiation of PDLSCs and explore the underlying mechanism. Results: H/R downregulated osteogenic indicators (collagen-I, RunX2, and ALP) in hPDLSCs (P < .01). In addition, the osteogenic capacity was found to be associated with the degree of H/R injury. FoxO1 positively regulated the osteogenic differentiation of PDLSCs (P < .01), and FoxO1 overexpression restored the osteogenic capacity of PDLSCs after H/R injury (P < .01). Further studies revealed that the heme oxygenase-1 signalling pathway was involved in FoxO1-mediated osteogenesis in PDLSCs. Conclusion: In H/R, PDLSCs exhibited proliferative capacity and impaired osteogenic differentiation, which could be reversed by FoxO1 overexpression. Mechanistically, FoxO1 removed reactive oxygen species by regulating the expression of heme oxygenase-1, thereby enhancing the osteogenic differentiation of PDLSCs. Clinical relevance: Given the positive effect of FoxO1 in alveolar bone remodelling in H/R, it could serve as a potential target for the treatment of periodontitis in patients with obstructive sleep apnea.